Obstetric capacity strengthening in Ghana results in wide geographic distribution and retention of certified Obstetrician/Gynaecologists: A quantitative analysis. (24th April 2022) - Kekulawala, Melani; Samba, Ali; Braunschweig, Yael; Plange‐Rhule, Jacob; Turpin, Cornelius; Johnson, Timothy R. B.; Anderson, Frank W. J.
Abstract: Objectives: To determine the cumulative retention of Obstetricians/Gynaecologists (Ob/Gyns) since the inception of the Ghana postgraduate Ob/Gyn programmes, to determine the demographic and practice characteristics of all Ob/Gyns who have been trained, and to compare the geographic distribution of Ob/Gyns throughout Ghana between 2010, when a previous study was conducted, and the current practice locations of all graduates in 2017. Design: Cross‐sectional, quantitative investigation. Setting: Fieldwork for this study was conducted in Ghana between 21 June 2017 and 20 August 2017. Methods: A roster of certified Ob/Gyns, year certified and email contact information was obtained from the Ghana College of Physicians and Surgeons, a roster of practice locations was obtained from Ghana Medical Board. Main outcome measures: Retention of Ob/Gyns, geographic distribution of providers and comparison of geographic spread between 2010 and 2017 practice locations. Results: Significant geographic spread and increase in in‐country medical programmes have occurred over the 7‐year period. In recent years, Ob/Gyn certifications through the Ghana College of Physicians and Surgeons have significantly increased. Conclusion: The establishment of the Ghana College of Physicians and Surgeons created a national certification opportunity that made Ob/Gyn certification more accessible. This provides a cadre of certified Ob/Gyns that can be trained and retained in low‐income settings, and allows for long‐term commitment in multiple relevant sectors that may serve to establish a comprehensive obstetric and gynaecology capacity beyond urban centres.